From Critical Diagnosis to Progressive Reconstruction: An Integrative Model of Future-Oriented Indonesian Legal Development - Wachid Baihaqi; Mukhsin Achmad (Kartika: Jurnal Studi Keislaman, 2026)
This article proposes an integrative model for future-oriented legal development in Indonesia by combining critical legal theory and progressive law within a unified analytical and prescriptive framework. Legal reform in Indonesia has predominantly focused on normative and procedural adjustments, yet persistent structural problems remain, including weak management of legal pluralism, the dominance of formalism, institutional bias, and unequal access to justice. This study employs normative legal research using conceptual, statutory, and historical-contextual approaches. Critical legal theory is applied as a diagnostic instrument to uncover power relations and structural injustices embedded in legal design and practice. Progressive law is subsequently positioned as a prescriptive framework to reconstruct law toward substantive justice through contextual interpretation and the protection of vulnerable groups. To ensure accountability and prevent subjectivism, the proposed model incorporates an accountability lock-in mechanism grounded in substantive rule of law, constitutional control, and reason-giving requirements. This study contributes both theoretical insight and a practical roadmap for developing a more just and accountable legal system in Indonesia.